2018
DOI: 10.2465/jmps.180409
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–induced phase transitions of Zn<sub>2</sub>SiO<sub>4</sub> III and IV studied using in–situ Raman spectroscopy

Abstract: Recent structural study of the high-pressure Zn 2 SiO 4 phases III and IV has suggested that they are retrograde phases formed during decompression. To clarify the stabilities of these phases under pressure, in-situ highpressure Raman spectroscopic measurements were taken at room temperature. Phase III, having a 'tetrahedral olivine' structure, transformed to a new phase at 5.5 GPa during compression and returned to phase III at 1.7 GPa during decompression. Phase IV also exhibited a phase transition at 2.5 GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As noted before, phases III and IV are "experimentally" observed at a pressure range between 8 to 11 GPa in the recovered samples [1]. In-situ Raman spectroscopic study [11] has demonstrated that phases III and IV transformed to the structure-unknown high-pressure phases (III-HP and IV-HP) at 5.5 and 2.5 GPa during compression, respectively. Therefore, there must be two stable phases corresponding those phases between phases II and V. However, no lowest enthalpy phases other than phase V were detected at pressure corresponding to synthesis of phases III and IV (8 to 11 GPa).…”
Section: Stability Of Phases and Possible High-pressure Candidatesmentioning
confidence: 54%
See 2 more Smart Citations
“…As noted before, phases III and IV are "experimentally" observed at a pressure range between 8 to 11 GPa in the recovered samples [1]. In-situ Raman spectroscopic study [11] has demonstrated that phases III and IV transformed to the structure-unknown high-pressure phases (III-HP and IV-HP) at 5.5 and 2.5 GPa during compression, respectively. Therefore, there must be two stable phases corresponding those phases between phases II and V. However, no lowest enthalpy phases other than phase V were detected at pressure corresponding to synthesis of phases III and IV (8 to 11 GPa).…”
Section: Stability Of Phases and Possible High-pressure Candidatesmentioning
confidence: 54%
“…These two phases show very similar compressional behaviors (Figure 1). Kanzaki [11] observed a phase transition of phase III to III-HP at 5.5 GPa during compression. So natural question is that phase III-Pbam corresponds to phase III-HP?…”
Section: "Phase Transitions" Observed During Structure Optimizationsmentioning
confidence: 99%
See 1 more Smart Citation